Teacher's Strategy In Learning Tilawah Of The Qur'an At MTs Nahdhatul Islam Mancang - Farida Khairani Siregar; Hasrian Rudi Setiawan (Yayasan Rahmat Islamiyah, 2023)
The purpose of this study was to find out how the teacher's strategy in learning recitations of the Qur'an at MTs Nahdhatul Islam Mancang. The method chosen is descriptive qualitative method. This research was conducted at MTs Nahdatul Islam Mancang. Data that can be obtained from teaching results, observations, interviews conducted with the principal and all MTs Nahdhatul Islam Mancang staff. Based on the data I can get that students can and are able to take part in learning in recitations of the Qur'an, this research shows that their level of enthusiasm in participating in learning recitations of the Qur'an is very high through the strategy carried out by the MTs Nahdhatul Islam Mancang, Kab. Langkat.